O cerco da universidade - Dagnino, Renato Peixoto, 1948- (1983)
Abstract: Research fomentation arose in the University after the 60th decade when the deficient internal technological ability and the lack of qualified staff were recognized, inclusive to handle imported technology. However, nowadays crisis in University's research activities is due not only to the gradual decrease of governmental resources, but also to the productive sector 's incapacity to establish a link with the University. So, while private enterprises didn't even take notice of University's research, state enterprises decided to proceed with technological importation or develop it on their own R & D centers